2020
DOI: 10.1186/s13613-020-00698-0
|View full text |Cite
|
Sign up to set email alerts
|

Impact of prior antibiotics on infected pancreatic necrosis microbiology in ICU patients: a retrospective cohort study

Abstract: Background: Recent guidelines advise against prophylactic antibiotics in patients with necrotizing pancreatitis, advocating instead a step-up drainage and necrosectomy strategy with antibiotics as dictated by microbiological findings. However, prompt antibiotic therapy is recommended in patients with sepsis or septic shock, a possible presentation of infected pancreatic necrosis (IPN). Consequently, in many critically ill patients with IPN, pancreatic samples are collected only after broad-spectrum antibiotic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
12
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 45 publications
(100 reference statements)
1
12
0
Order By: Relevance
“…Consistent with the previous analysis of infections, our microbiologic result demonstrated that bloodstream (n = 32) was the most common extra-pancreatic site of MDR- K. pneumoniae infections which may verify our hypothesis for bacterial translocation to the bloodstream [ 32 ]. According to previous studies, drug resistance of MDR- K. pneumoniae pathogens causing AP secondary infections was quite serious [ 5 , 15 ].…”
Section: Discussionsupporting
confidence: 91%
“…Consistent with the previous analysis of infections, our microbiologic result demonstrated that bloodstream (n = 32) was the most common extra-pancreatic site of MDR- K. pneumoniae infections which may verify our hypothesis for bacterial translocation to the bloodstream [ 32 ]. According to previous studies, drug resistance of MDR- K. pneumoniae pathogens causing AP secondary infections was quite serious [ 5 , 15 ].…”
Section: Discussionsupporting
confidence: 91%
“…Overused prophylactic antibiotic treatments for 'suspected' IPN could result in the acquisition of MDR or carbapenem resistance [1]. Precious studies reported that CRE, as a mainly infectious MDR pathogen, has spread worldwide and influenced the outcome of IPN patients especially in India and China [7,[12][13][14][15][16].…”
Section: Introductionmentioning
confidence: 99%
“…The use of amoxicillinclavulanate was not significantly different between the two groups (22 (29%) vs. 3 (13%), p = 0.174), while piperacillin/ tazobactam or carbapenems were more frequently administered in the exposed group than in the unexposed group (15/23 (65%) vs. 28/77 (36%), respectively p = 0.0175). Interestingly, the severity scores were similar in patients receiving piperacillin/tazobactam or carbapenems vs. the other patients (SAPS-II: 27 [22][23][24][25][26][27][28][29][30][31][32][33][34][35][36] vs. 28 [23][24][25][26][27][28][29][30][31][32][33][34][35][36][37][38], p = 0.542; SOFA score: 4 [3][4][5][6] vs. 5 [4][5][6][7], p = 0.085). Moreover, in the specific group of patients exposed to antimicrobial therapy, no difference was found between patients receiving these regimens and the other patients (SAPS-II: 25 [21-37] vs. 23 [21-32], p = 0.332; SOFA score: 4 [3][4][5][6] vs. 5 [3][4]…”
Section: Antimicrobial Therapy and Bacterial Speciesmentioning
confidence: 88%
“…Several studies addressed this issue, all of them out of the field of NSTI. In a study by Garret et al involving 137 patients with necrotizing pancreatitis, the proportion of patients developing an infection from pancreatic samples with MDR bacteria was similar in the exposed and unexposed groups (24 and 26%, respectively; p = 0.99) [ 25 ]. The results of other studies are more controversial.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation